2023
DOI: 10.1097/cej.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune gastritis serological biomarkers in gastric cancer patients

Petra Kriķe,
Meret Sophia Appel,
Zakera Shums
et al.

Abstract: The role of autoimmunity in the pathogenesis of gastric cancer remains controversial. We studied antiparietal cell antibody (anti-PCA) and anti-intrinsic factor antibody (anti-IFA) levels and their associations with pepsinogen I/pepsinogen II levels in patients with gastric adenocarcinoma compared to a control group with mild or no atrophy of the stomach mucosa. Plasma levels of anti-PCA and anti-IFA were measured by ELISA (Inova Diagnostics Inc, San Diego, California, USA). The cutoff value for anti-PCA and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Serologic markers of AAG include anti-parietal cell antibodies and anti-intrinsic factor antibodies [30]. The sensitivity and specificity of anti-parietal cell antibodies for the diagnosis of AAG are 81% and 90%, respectively, whereas anti-intrinsic factor antibodies have poor sensitivity (27%) and high specificity (100%) [1].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Serologic markers of AAG include anti-parietal cell antibodies and anti-intrinsic factor antibodies [30]. The sensitivity and specificity of anti-parietal cell antibodies for the diagnosis of AAG are 81% and 90%, respectively, whereas anti-intrinsic factor antibodies have poor sensitivity (27%) and high specificity (100%) [1].…”
Section: Diagnosismentioning
confidence: 99%
“…Similar results were reported by another prospective cohort study aimed at evaluating the natural history of autoimmune gastritis in 498 patients with AAG at any stage. During the median follow-up time of 52 months, newly onset neoplastic complications occurred in 41/498 patients (8.5%); in particular, NETs [30] and epithelial dysplasia (18), but no cases of gastric adenocarcinoma, were reported [20]. Murine models showed that M2-macrophages are a pro-carcinogenic immune infiltrate that is crucial for the progression from metaplasia to dysplasia [61].…”
Section: Risk Of Malignancymentioning
confidence: 99%
“…Потенциал АИГ как предракового заболевания требует дальнейшего изучения. P. Kriķe et al у пациентов с диагнозом аденокарциномы желудка не обнаружили более частого выявления антител к париетальным клеткам и к внутреннему фактору по сравнению с контрольной группой [17]. При длительном наблюдении за пациентами АИГ без инфекции H. pylori в анамнезе не было установлено повышения риска рака желудка по сравнению с контрольной группой, и авторы предполагают, что этот риск может быть ассоциирован именно с предшествующей или нераспознанной текущей инфекцией H. pylori [18].…”
unclassified